Pengaruh return on equity (ROE), net profit margin (NPM), return on risked asset (RORA), dan leverage terhadap devident payout ratio pada indeks MNC36 yang terdaftar di Bursa Efek Indonesia - Napitupulu, Ferdinand; Marbun, Reinaldi; Natami, Putri; Namira, Namira; Mariana, Mariana (Jurnal Paradigma Ekonomika, 2022)
The study aims to see how relationships are individually or concurrent with the title of influence return on equity, net profit margin, return on risked assets, and leverage against dividend payout ratio in the MNC36 index listed on the Indonesia stock exchange. This research observation uses purposive sampling with a partial testing (T-Test), simultaneous test (F-test), and adjusted R square test. The test results for this observation are (1) Return on equity had a negative but not profound effect on dividend payout ratio. (2) Net profit margin has a negative but profound effect on dividend payout ratio (3) Return on risked assets has no effect and no significance to dividend payout ratio. (4) Leverage had a negative but not profound effect on the dividend payout ratio. With the adjusted R square of 27.9% and influenced by other variables of the same magnitude, 72.1%. Then the overall result return on equity, net profit margin, return on risked assets, and leverage has simultaneous effects on the dividend payout ratio on the MNC36 index listed on the Indonesia stock exchange.